A mutation in the major autophagy gene, WIPI2, associated with global developmental abnormalities - Musharraf Jelani; Hannah C. Dooley; Andrea Gubaš; Hussein Sheikh Ali Mohamoud; Muhammad Tariq Masood Khan; Zahir Ali; Changsoo Kang; Fazal Rahim; Amin Jan; Nirmal Vadgama; Muhammad Ismail Khan; Jumana Y. Al‐Aama; et al. (2019)
We describe a large consanguineous pedigree from a remote area of Northern Pakistan, with a complex developmental disorder associated with wide-ranging symptoms, including mental retardation, speech and language impairment and other neurological, psychiatric, skeletal and cardiac abnormalities. We initially carried out a genetic study using the HumanCytoSNP-12 v2.1 Illumina gene chip on nine family members and identified a single region of homozygosity shared amongst four affected individuals on chromosome 7p22 (positions 3059377-5478971). We performed whole-exome sequencing on two affected individuals from two separate branches of the extended pedigree and identified a novel nonsynonymous homozygous mutation in exon 9 of the WIPI2 (WD-repeat protein interacting with phosphoinositide 2) gene at position 5265458 (c.G745A;pV249M). WIPI2 plays a critical role in autophagy, an evolutionary conserved cellular pathway implicated in a growing number of medical conditions. The mutation is situated in a highly conserved and critically important region of WIPI2, responsible for binding PI(3)P and PI(3,5)P2, an essential requirement for autophagy to proceed. The mutation is absent in all public databases, is predicted to be damaging and segregates with the disease phenotype. We performed functional studies in vitro to determine the potential effects of the mutation on downstream pathways leading to autophagosome assembly. Binding of the V231M mutant of WIPI2b to ATG16L1 (as well as ATG5-12) is significantly reduced in GFP pull-down experiments, and fibroblasts derived from the patients show reduced WIPI2 puncta, reduced LC3 lipidation and reduced autophagic flux.